ANALISIS AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (AKIP) BADAN PERENCANAAN PEMBANGUNAN, PENELITIAN DAN PENGEMBANGAN DAERAH KABUPATEN MINAHASA - Tambajong, Marco Hendri; Ilat, Ventje; Wokas, Heince R. N. (Universitas Sam Ratulangi, 2023)
This study aims to determine the performance aniani4d accountability of agencies for development planning, research and regional development in Minahasa Regency. This research method uses a case study or case study as a research approach. The case study approach is used because it digs deeper and more information than the exploratory and explanatory approaches. The researcher will conduct interviews with related parties such as officials or personnel involved in the preparation and those who carry out the review and evaluation of the Performance Accountability of Government Agencies in the Minahasa Regency Regional Development Planning, Research and Development Agency to obtain information related to research problems. The results of this study indicate that the implementation of SAKIP at the Minahasa Regency Regional Development Planning, Research and Development Agency has been carried out, but there are still deficiencies and weaknesses that need to be followed up. there is an increase in output and outcome performance as well as other performance compared to the previous year, namely from a score of 52.82 in 2020 with the CC Category, to a score of 63.35 in 2021 with category B, Performance Measurement has been carried out but has not been used as a basis for awarding rewards and Punishment and strategy adjustments in achieving effective and efficient performance.